The importance of reliability of machine on operational improvement : a case study - Juliana, Md Nor (2016)
The study investigated the measurement of machine reliability and determines the machine that need for improvement in Stationery Company in Kuantan. There is a need to show how reliability of machines could contributed to the overall operational objective the reliability of machine is closely related to the maintenance. Hence, the improvement method that initiated in Japan which is Total Productive Maintenance (TPM) was the essential method that being used by most industry. During this study, the time losses that were observed in the production for the first 5 working days in September 2015 were recorded and calculated the three main factors contributed to Overall Equipment Effectiveness (OEE).Three machines that regularly used in production is chosen. Based on this study, we knew that the machines need for improvement since the OEE recorded was lower than 85%. A more detailed data collection should be carried out for future research after the implementation of TPM in order to obtain more accurate result.